Moisture diffusivity in high oleic sunflower seeds and kernels - Santalla, Estela (2010)
Moisture diffusivities in high oleic seeds and kernels were obtained from experimental thin layer drying rates in the range of 25-90°C air temperature and 4.2-33.5% initial moisture content (d.b.). Moisture diffusivity back-calculated from Ficks second law of diffusion var- ied between 0.85.10⁻¹⁰ and 7.26.10⁻¹⁰ m²/s for seeds and between 0.37.10⁻¹⁰ and 2.39.10⁻¹⁰ m²/s for kernels. The Arrhenius activation energy for seeds and kernels resulted 31 and 24 kJ/mol, respectively. A new model based on the kinetic parameter of Page equation was proposed as a simple tool to predict water diffusion in high oleic sunflower seeds and kernelss.